Temporal and spatial variation in predation on juvenile herring (Clupea harengus L.) by Northeast Arctic cod (Gadus morhua L.) in the Barents Sea in 1984-1997 - Johansen, Geir Odd (ICES Journal of Marine Science, 2002)
Previous studies indicate that predation by Northeast Arctic cod is an important cause of natural mortality of juvenile Norwegian spring-spawning herring in the Barents Sea. In this paper broad scale temporal and spatial variation in the predator–prey interaction between these two species in the Barents Sea was analysed. The analysis was based on cod stomach data from this area in 1984–1997. The predator–prey interaction between cod and juvenile herring in the Barents Sea was highly variable in time and space. On a yearly basis the most intense predation occurred in years with strong year classes of herring in the Barents Sea. Intensity of predation increased with decreasing abundance of capelin. Seasonal variation in intensity of predation on juvenile herring was low. Maps of the spatial distribution of cod feeding on herring illustrated a difference between the first and second halves of the year. In late winter and spring herring was consumed by cod in a restricted area in the southern part of the Barents Sea. In late summer, autumn and early winter herring was consumed by cod in a wide area south of the Polar Front. Climatic variation influenced the spatial distribution in the second half of the year. The results were discussed in the context of broad scale ecosystem dynamics in the Barents Sea.